Handbook of interpersonal communication - Antos, Gerd; Ventola, Eija; Weber, Tilo, 1964- (Handbooks of applied linguistics, 2008)
In todays globalized world of international contact and multicultural interaction, effective intercultural communication is increasingly seen as a pre-requisite for social harmony and organisational success. This handbook takes a 'problem-solving' approach to the various issues that arise in real-life intercultural interaction. The editors have brought together experts from a range of disciplines, including linguistics, psychology and anthropology, to provide a multidisciplinary perspective on the field, whilst simultaneously anchoring it in applied linguistics. Key features: provides a state-